2019
DOI: 10.7150/jca.32022
|View full text |Cite
|
Sign up to set email alerts
|

BDH2 is downregulated in hepatocellular carcinoma and acts as a tumor suppressor regulating cell apoptosis and autophagy

Abstract: BDH2 is a short-chain dehydrogenase/reductase family member involved in several biological and pathological processes, including the utilization of cytosolic ketone bodies, immunocyte regulation and tumor progression. In this study, we first revealed that BDH2 was downregulated in HCC tissues by qRT-PCR and immunohistochemistry analysis and that low BHD2 expression was significantly associated with poor overall survival, poor tumor differentiation, increased tumor size, venous invasion and an advanced BCLC sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…AMPK, MAPK/Erk1/2, and PI3K/Akt/mTOR signalling pathways are classic apoptosis and autophagy pathways [28][29][30]. Previous studies have shown that BDH2 inhibits HCC cell growth, proliferation, and migration by inducing apoptosis and autophagy [31]. However, the specific molecular mechanisms of BDH2-induced apoptosis and autophagy remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, MAPK/Erk1/2, and PI3K/Akt/mTOR signalling pathways are classic apoptosis and autophagy pathways [28][29][30]. Previous studies have shown that BDH2 inhibits HCC cell growth, proliferation, and migration by inducing apoptosis and autophagy [31]. However, the specific molecular mechanisms of BDH2-induced apoptosis and autophagy remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria: (1) studies were focused on the correlation between leptin or AdipoQ levels and HCC risk, and provided full text and complete data in HCC patients and cancer-free controls (CFC), or (2) investigated the correlation between AdipoQ or leptin levels and the prognosis of HCC, and provided sufficient information to get the hazard ratio (HR) and 95% confidence intervals (CIs). Exclusion criteria: conference abstracts, case reports, comments, review, and experimental animal studies were excluded.…”
Section: Study Selection Criteriamentioning
confidence: 99%
“…Inclusion criteria: studies (1) were focused on the correlation between leptin or AdipoQ levels and HCC risk, and provided full text and complete data in HCC patients and controls, or (2) investigate the correlation between AdipoQ or leptin levels and the prognosis of HCC, and provide su cient information to get the hazard ratio (HR) and 95% con dence intervals (CIs). Exclusion criteria: conference abstracts, case reports, comments, review, editorials, letters to the editor, and experimental animal studies were excluded.…”
Section: Study Selection Criteriamentioning
confidence: 99%
“…In 2018, hepatocellular carcinoma (HCC) became the sixth most common cancer in the world and the fourth leading cause of cancer death globally [1]. The pathogenesis of HCC is complicated and still unclear, the process is high invasion and aggression, and the prognosis is very poor [2]. HCC is generally secondary to liver cirrhosis or viral hepatitis.…”
Section: Introductionmentioning
confidence: 99%